A Three-term Conjugate Gradient Descent Method With Some Applications - Ahmad Alhawarat; Zabidin Salleh; Hanan Alolaiyan; Hamid El Hor; Shahrina Ismail (Springer open journal, 2025)
Indexed by WOS/Scopus/ERA